Influence of Sarcopenia on the Effect of Exercise Therapy for Elderly Patients with Chronic Low Back Pain - Masafumi Nakagawa; Mamoru Kawakami; Masatoshi Teraguchi; Ryohei Kagotani; Yoshimasa Mera; Tadashi Sumiya; Masakazu Minetama; Yoshio Yamamoto; Sachika Matsuo; Nana Sakon; Tomohiro Nakatani; Tomoko Kitano; et al. (Spine Surgery and Related Research, 2020)
Introduction: Sarcopenia, a condition characterized by decreased skeletal muscle mass, has increasingly been attracting attention in Japan, which has an aged society. The association between chronic low back pain (CLBP) and muscle mass is important. This study aimed to investigate the effect of exercise therapy for CLBP with or without sarcopenia. Methods: This study was a prospective cohort study. Patients who were aged >65 years during 2017-2018 and had CLBP, with pain lasting >12 weeks and pain intensity being 3, were included in the study. The patients were divided into two groups: sarcopenia (S) and nonsarcopenia (NS) groups. The numerical rating scale (NRS) for pain intensity, Roland-Morris Disability Questionnaire (RMDQ), Japanese Orthopaedic Association Back Pain Evaluation Questionnaire (JOABPEQ), Hospital Anxiety and Depression Scale (HADS), trunk muscle strength, a European Quality of Life instrument, and an NRS of treatment satisfaction were assessed. All patients underwent a high-intensity exercise therapy during 2 weeks of hospitalization and were followed up for 1 and 3 months. Results: Twenty-eight patients with CLBP were included. The prevalence rate of sarcopenia was 42.9%. The NRS and RMDQ scores and gait function were clinically improved at the end points in all patients with or without sarcopenia. Moreover, high treatment satisfaction was achieved. The quality of life, treatment satisfaction, psychological disorder subscale score of the JOABPEQ, and HADS score tended to be lower in the S group than in the NS group. Conclusions: Our short-term exercise therapy was effective for low back pain, disability, and gait disturbance in elderly patients with CLBP with or without sarcopenia. However, the prevalence of sarcopenia was high in elderly patients with CLBP. Although low back pain and disability in patients in the S group were improved by exercise therapy, their quality of life and treatment satisfaction might be lower than those of patients without sarcopenia.